Instrumentação, modelagem, controle e supervisão de um sistema de bombeamento de água e módulo turbina-gerador - Bruno Henrique Barbosa (2006)
This work describes the design, instrumentation, modeling, control and supervision of a hidraulic process (which can be divided into two subsystems, namely: water pumping system and turbine test prototype). The design of the hidraulic process (compounded by two centrifugal pumps, a Francis turbine, and hidraulic pipes) had been already accomplished and partially implemented before the beginning of this work. However, the turbine test prototype design (consisted of a direct current generator besides other components), as well as the instrumentation system for the hidraulic process and the computer-based data acquisition system were implemented during this master's thesis. After the construction and instrumentation of the pilot plant, a data acquisition system was developed. In order to reduce noise effects, two electronic boards were built. A data acquisition board from Advantech Co. Ltda. and the Labview software were used in this context. The static characteristics of the system were assessed from experimental data acquired from the process. Non-linear dynamic models were identified, for some of them a priori information were used regarding the obtained static characteristics by means of optimization tools during parameters estimation stage. Finally, a closed-loop system was developed, using a PI controller. The Ziegler-Nichols method was applied in the non-linear dynamic models for tunning the controller gains.